Prevalence and Characteristics of Penile Cancer in Karangasem Regency, Indonesia, 2020-2022 - Kurniawan, I Putu Adi; Suyandnya, I Made (Cermin Dunia Kedokteran, 2024)
Background: Indonesia reported 1,143 penile carcinoma cases from 2004 to 2013. Bali reported the highest age-standardized incidence rate (ASR) in 2004-2013. Method: A quantitative descriptive retrospective study was conducted at Karangasem General Hospital and Balimed Karangasem Hospital. Results: This study involved 29 patients diagnosed with penile cancer in 2020-2022. The highest number of cases was found in 2020. Most cases were in the 60-69 year age-group (34.5%), with a low educational level (75.9%), a smoking habit (75.9%), no history of circumcision (100%), and squamous cell carcinoma (86.2%). The treatment was mainly partial penectomy (41.3%). Conclusion: The study found that the highest prevalence of penile cancer was 6.02 per 100,000 people in 2020.